New families of Jacobsthal and Jacobsthal-Lucas numbers - Catarino, P.; Vasco, P.; Campos, H.; Aires, A.P.; Borges, A. (Algebra and Discrete Mathematics, 2015)
In this paper we present new families of sequences that generalize the Jacobsthal and the Jacobsthal-Lucas numbers and establish some identities. We also give a generating function for a particular case of the sequences presented.